PENGARUH SUPERVISI, MOTIVASI DAN KEDISIPLINAN TERHADAP KINERJA GURU DI SMA NEGERI 1 KARANGANYAR - Sumarsono, Hadi -; Sriwidodo, Untung - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2010)
ABSTRACT The aims of this research are: 1.to analyze the significance effect of supervision, motivation and discipline variables to the teachers’ work at SMA Negeri 1 Karanganyar. 2. to analyze the significance of the simultaneous effect of the supervision, motivation and discipline variables to teachers’ work at SMA Negeri 1 Karanganyar. 3. to analyze of the dominant effect of supervision, motivation and discipline variables to the teachers’ work at SMA Negeri 1 Karanganyar. The results of partial regression test (t test) show that: variable of supervision does not significantly affect to the teachers’ work at SMA Negeri 1 Karanganyar. Variable of motivation does not significantly affect to the teachers’ work at SMA Negeri 1 Karanganyar. Variable of discipline significantly affects to the teachers’ work at SMA Negeri 1 Karanganyar. The result of F Test shows that the probability value is 0,000 ª < 0,05, so Ho is rejected. It means that there is significant influence of supervision, motivation and dischipline variables to the teachers’ work at SMA Negeri 1 Karanganyar. The result of determination coefficient test shows that adjusted R Square value is 0,440. It means that the precentage of the infuence of variable of supervision, motivation and discipline to the teachers’ works at SMA Negeri 1 Karanganyar is 44 percent. Keywords: Supervision, motivation, discipline, work achievement.